Rationale and Study Design to Assess the Efficacy and Safety of Minocycline in Patients with Moderate to Severe Acute Ischaemic Stroke (EMPHASIS) - Liping Liu; Yongjun Wang; Yilong Wang; Xingquan Zhao; Yao Lu; Philip M Bath; Xiaoling Liao; Yuesong Pan; S Claiborne Johnston; Pierre Amarenco; Ling Guan; Hui Qu; et al. (Stroke and Vascular Neurology)
Background Inflammation and blood-brain barrier disruption may contribute to the pathogenesis of ischaemic stroke. Minocycline was shown to exert anti-inflammatory effects by attenuating microglial activation and protecting blood-brain barrier in preclinical studies. Previous small-scale clinical studies have suggested that minocycline may have a potential beneficial effect on prognosis in acute ischaemic stroke. However, the efficacy and safety of minocycline in patients with acute ischaemic stroke need to be further confirmed.Study aims We designed the study, Efficacy and Safety of Minocycline in Patients with Moderate to Severe Acute Ischaemic Stroke (EMPHASIS), to evaluate the effect of minocycline in improving the functional outcome and the drug safety in patients with acute ischaemic stroke.Methods The EMPHASIS study is a multicentre, randomised, double-blind, placebo-controlled trial aiming to recruit patients with acute ischaemic stroke. Patients who had ischaemic stroke within 72 hours of onset, a National Institutes of Health Stroke Scale score between 4 and 25 and Ia≤1 (moderate-to-severe) will be randomly allocated to either minocycline or placebo groups in a 1:1 ratio. Patients will receive minocycline (or placebo) with a loading dose of 200 mg, and subsequent 100 mg every 12 hours for 4 days. All patients will receive routine guideline-based treatment. The primary efficacy outcome is an excellent functional outcome assessed by the proportion of modified Rankin Scale score of 0–1 at 90±7 days. The main safety outcomes include the number of symptomatic intracranial haemorrhage at 24±2 hours and 6±1 days.Discussion The EMPHASIS trial is the first phase III trial to investigate whether minocycline is effective and safe in improving functional outcome at 90 days in patients with moderate-to-severe acute ischaemic stroke. The data generated may provide valuable evidence of a potential anti-inflammation treatment for ischaemic stroke.